2016
DOI: 10.1177/1745505716658898
|View full text |Cite
|
Sign up to set email alerts
|

Early spontaneous multiple fetal pregnancy reduction is associated with adverse perinatal outcomes in in vitro fertilization cycles

Abstract: The primary objective of this study is to investigate whether early spontaneous multiple fetal pregnancy reduction, also known as vanishing twin syndrome, is associated with adverse perinatal outcomes in fresh in vitro fertilization cycles. This is a retrospective cohort study of women with live singleton births with and without an early vanishing twin after fresh in vitro fertilization. Characteristics compared included incidence of preterm birth, overall birth weight, overall low birth weight, overall very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 23 publications
0
13
2
1
Order By: Relevance
“…Previous studies have compared pregnancy outcomes among ART singletons with VTS to either ART singletons without VTS or ART multiples ( Pinborg et al , 2005 , 2007 ; Shebl et al , 2008 ; Luke et al , 2009 ; Almog et al , 2010 ; Sazonova et al , 2011 ; Davies et al , 2016 ; Petrini et al , 2016 ; Zhou et al , 2016 ). The studies of ART singletons found reductions in birth weight with a vanishing twin ranging from 89 to 373 g ( Pinborg et al , 2005 ; Shebl et al , 2008 ; Almog et al , 2010 ; Sazonova et al , 2011 ; Petrini et al , 2016 ). Two studies reported an increased risk of SGA similar to our findings, with ORs of 1.50 and 2 ( Pinborg et al , 2007 ; Shebl et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have compared pregnancy outcomes among ART singletons with VTS to either ART singletons without VTS or ART multiples ( Pinborg et al , 2005 , 2007 ; Shebl et al , 2008 ; Luke et al , 2009 ; Almog et al , 2010 ; Sazonova et al , 2011 ; Davies et al , 2016 ; Petrini et al , 2016 ; Zhou et al , 2016 ). The studies of ART singletons found reductions in birth weight with a vanishing twin ranging from 89 to 373 g ( Pinborg et al , 2005 ; Shebl et al , 2008 ; Almog et al , 2010 ; Sazonova et al , 2011 ; Petrini et al , 2016 ). Two studies reported an increased risk of SGA similar to our findings, with ORs of 1.50 and 2 ( Pinborg et al , 2007 ; Shebl et al , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to IVF/ICSI pregnancies, it is estimated to occur in 12–30% ( Gjerris et al , 2012 ). Furthermore, VTS is associated with adverse pregnancy outcomes for the remaining survivor among both spontaneously conceived ( Evron et al , 2015 ) and ART pregnancies ( Pinborg et al , 2005 , 2007 ; Shebl et al , 2008 ; Luke et al , 2009 ; Almog et al , 2010 ; Sazonova et al , 2011 ; Davies et al , 2016 ; Petrini et al , 2016 ; Zhou et al , 2016 ). Adverse outcomes include higher risk of low birth weight, preterm birth, small for gestational age (SGA) and birth defects.…”
Section: Introductionmentioning
confidence: 99%
“…First, only ICSI cycles were included in the current study, which reflects up to 80% of the overall patient population undergoing ART at our center. However, it is worthwhile to note that similar trends in PTB and LBW have been reported in patients undergoing in vitro fertilization using smaller sample sizes in internal [45] and external investigations [39,40]. Second, a mean of 3.01 embryos were transferred in the current study.…”
Section: Discussionmentioning
confidence: 56%
“…Only patients with live singleton birth were included. The diagnosis of early VT was made based on criteria described by Petrini et al [15]. In brief, patients with a positive β -human chorionic gonadotropin (hCG) level on cycle day (CD) 28 underwent a transvaginal sonogram on CD 49 to record the number of fetal poles with cardiac activity in the respective gestational sacs [15].…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of early VT was made based on criteria described by Petrini et al [15]. In brief, patients with a positive β -human chorionic gonadotropin (hCG) level on cycle day (CD) 28 underwent a transvaginal sonogram on CD 49 to record the number of fetal poles with cardiac activity in the respective gestational sacs [15]. Patients with spontaneous in utero reduction of one or more embryos before CD 49 were considered to have an early VT. For this study, we only included embryos that spontaneously reduced within the first trimester.…”
Section: Methodsmentioning
confidence: 99%